Relationship of indicators of oxygen-containing blood elements with the duration of systematic triathlon training for amateur athletes - Kovelskaya, A.; Gorenko, Z.; Ocheretko, B. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to investigate the nature of changes in the indicators of oxygen-containing blood elements in amateur athletes with different duration of systematic triathlon training.